Broadband spectral verification of optical clearing reversibility in lung tissue. Issue 1 (23rd August 2022) - Oliveira, Luís R.; Ferreira, Ricardo M.; Pinheiro, Maria R.; Silva, Hugo F.; Tuchin, Valery V.; Oliveira, Luís M.
Abstract: The increase of tissue transparency through sequential optical immersion clearing treatments and treatment reversibility have high interest for clinical applications. To evaluate the clearing reversibility in a broad spectral range and the magnitude of the transparency created by a second treatment, the present study consisted on measuring the spectral collimated transmittance of lung tissues during a sequence of two treatments with electronic cigarette (e‐cig) fluid, which was intercalated with an immersion in saline. The saline immersion clearly reverted the clearing effect in the lung tissue in the spectral range between 220 and 1000 nm. By a later application of a second treatment with the e‐cig fluid, the magnitude of the optical clearing effect was observed to be about the double as the one observed in the first treatment, showing that the molecules of the optical clearing agent might have converted some bound water into mobile water during the first treatment. Abstract : The evaluation of sequential tissue immersion clearing treatments and treatment reversibility has great interest. Measuring the spectral transmittance of lung samples between 220 and 1000 nm, it was verified that the transparency created by electronic cigarette (e‐cig) fluid in the first 30 minutes was completely reversed after 8 minutes of sample immersion in saline and that a second treatment with e‐cig almost doubled the first transparency effect.